Development and validation of the pandemic fear perception and adaptability scale - Wang, Mu; Qi, Haiyan; Chen, Yanyan; Li, Mian (Frontiers in Psychology, 2025)
IntroductionIndividuals exhibit specific behavioral responses to fear and stress. The Pandemic Fear Perception and Adaptability Scale (PFPA) is a novel instrument designed to assess fear perception and behavioral adaptability in the context of pandemics.MethodsA cross-sectional survey was conducted with 923 participants in China to evaluate the psychometric properties of the PFPA. After expert review, a 7-item scale was developed, comprising three subscales: self-efficacy, perceived susceptibility, and perceived threat. Classical test theory, confirmatory factor analysis (CFA) and Rasch modeling were used to assess the scale’s reliability and validity.ResultsThe PFPA demonstrated good reliability, with an internal consistency (Cronbach’s α = 0.700) and test-retest reliability (ICC(2,1) = 0.781, p < 0.001). Evidence of validity was supported by an average variance extracted of 0.563 and a composite reliability of 0.898. CFA indicated excellent model fit (χ²(11) =15.123, p = 0.177; CFI = 0.998, GFI = 0.995, TLI = 0.995, RMSEA = 0.020). Differential item functioning analysis showed minimal bias across gender and age.DiscussionThis study establishes the PFPA as a reliable and valid tool for assessing fear perception and behavioral adaptability, with potential to evaluate these constructs in other pandemic contexts. Given its initial development in a Chinese context, future research should examine its applicability across diverse cultural and linguistic settings.